PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Guru SMA Negeri Sub Rayon 02 Kota Semarang) - 11.52.02.0119, Tri Ambawani (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aims to examine and analyze the effect of discipline and motivation on teacher performance with mediation on teacherâs job satisfaction Sub Rayon 02 SMA Negeri Semarang. This research uses field research, with a quantitative approach. The population in this study is the teachers who teach in high schools Semarang Sub Rayon 02 totaling 190 people. Samples were taken using proporsional random sampling technique of 129 teachers. Analysis techniques using multiple linear model testing analysis, R2 Test, F Test, hypothesis testing using the t test and the effects test mediation (path analysis).The results showed that: (1) discipline has positive and significant effect on job satisfaction (2) motivation has positive and significant effect on job satisfaction, (3) discipline has no effect on teacherâs performance,(4) motivation has positive and significant effect on the performance of teachers, (5) job satisfaction hasand significant effect on teacherâs performance, (6) job satisfaction mediates the effect of discipline on teacherâs performance, (7) job satisfaction, does not mediate the effect of motivation on teacherâs performance. Keywords: Discipline, Motivation, Job Satisfaction, and Performance of Teachers